Step
*
1
of Lemma
initseg_sum_shift
1. r : 
@i
2. u : 
@i
3. v : 
 List@i
 initseg_sum(r;[u / v]) = (u + initseg_sum(r - 1;v))
BY
{ Assert 
x:
. (x = (u + initseg_sum(r - 1;v)))
 }
1
.....assertion..... 
1. r : 
@i
2. u : 
@i
3. v : 
 List@i
 
x:
. (x = (u + initseg_sum(r - 1;v)))
2
1. r : 
@i
2. u : 
@i
3. v : 
 List@i
4. 
x:
. (x = (u + initseg_sum(r - 1;v)))
 initseg_sum(r;[u / v]) = (u + initseg_sum(r - 1;v))
Latex:
1.  r  :  \mBbbN{}@i
2.  u  :  \mBbbZ{}@i
3.  v  :  \mBbbZ{}  List@i
\mvdash{}  initseg\_sum(r;[u  /  v])  =  (u  +  initseg\_sum(r  -  1;v))
By
Assert  \mkleeneopen{}\mexists{}x:\mBbbZ{}.  (x  =  (u  +  initseg\_sum(r  -  1;v)))\mkleeneclose{}\mcdot{}
Home
Index